ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI YIELD OBLIGASI KORPORASI (STUDI KASUS PADA SELURUH PERUSAHAAN PENERBIT OBLIGASI YANG TERDAFTAR DI BEI PERIODE 2010-2012) - Aisah, Siti Hatanty; Haryanto, Mulyo (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to analyze the effect of interest rates, inflation rates, bond ratings, debt to equity ratio (DER), firm size and maturity on corporate bond yields. The returns will be accepted from profit of bonds are always moves fluctuated. Therefore, needs deeply observation to see how big the influences of variables are used.The population used in this research is all issuer bond companies were listed in BEI for year 2010-2012. The sample in this research is 37 bonds from 18 companies. Research method used is multiple linear regression models.The results showed those interest rates, bond rating, firm size and maturity have a significant effect on corporate bond yield. However debt to equity ratio (DER) has no significant effect on corporate bond yield. This research can be used as a reference for investors to predict the expected bond yields in the future and can be decision of investors to invest.